2013
DOI: 10.1007/s00436-013-3314-6
|View full text |Cite
|
Sign up to set email alerts
|

Critical swimming speed of brown trout (Salmo trutta) infested with freshwater pearl mussel (Margaritifera margaritifera) glochidia and implications for artificial breeding of an endangered mussel species

Abstract: Unionid freshwater mussels need to attach to a host fish for completion of their life cycle. It remains unclear whether the relationship between these mussels and their host fishes can be considered parasitic, mutualistic, or commensal. Herein, we studied the effects of Margaritifera margaritifera infestation on Salmo trutta, the most important host of this endangered mussel species in Central Europe. Glochidial load of host fish increased with increasing glochidial concentration, but the highest ratios of enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 28 publications
6
55
1
Order By: Relevance
“…As costs of FPM infection for the host have been documented (Meyers and Millemann 1977, Taeubert and Geist 2013, Thomas et al 2014, this finding supports the enemy release hypothesis (Sax andBrown 2000, Mitchell andPower 2003) whereby low infectivity by native parasites in invading species may provide a competitive advantage for the aliens over the native species which suffer more intensive parasitism. Thus, the inappropriateness of brook trout as a host for European FPM and its potential to invade FPM rivers and replace the native host of FPM, brown trout, especially in small headwater tributaries of northern Fennoscandia even within 2 decades (Korsu et al 2007, Spens et al 2007, Öhlund et al 2008) makes the spread of brook trout an additional, and previously unrecognized, potential threat to the European FPM.…”
Section: Suitability Of Brook Trout As a Host For The European Freshwsupporting
confidence: 72%
See 1 more Smart Citation
“…As costs of FPM infection for the host have been documented (Meyers and Millemann 1977, Taeubert and Geist 2013, Thomas et al 2014, this finding supports the enemy release hypothesis (Sax andBrown 2000, Mitchell andPower 2003) whereby low infectivity by native parasites in invading species may provide a competitive advantage for the aliens over the native species which suffer more intensive parasitism. Thus, the inappropriateness of brook trout as a host for European FPM and its potential to invade FPM rivers and replace the native host of FPM, brown trout, especially in small headwater tributaries of northern Fennoscandia even within 2 decades (Korsu et al 2007, Spens et al 2007, Öhlund et al 2008) makes the spread of brook trout an additional, and previously unrecognized, potential threat to the European FPM.…”
Section: Suitability Of Brook Trout As a Host For The European Freshwsupporting
confidence: 72%
“…Negative effects of FPM parasitism for the host, such as mortality (Meyers andMillemann 1977, Taeubert and, respiratory cost (Thomas et al 2014) and reduced ability to move (Taeubert and Geist 2013) or feed (Österling et al 2014) have been reported. On the other hand, the functional role of mussels in river ecosystems is undoubted; they filter plankton, bacteria, algae, detritus and even dissolved organic matter from the water column for feeding, thus purifying the water but also biodepositing these materials as pseudofaeces to the river bottom, thereby producing a nutrient-rich and easily assimilated food source for benthic invertebrates and thus supporting also salmonid production , Pusch et al 2001, Vaughn and Hakenkamp 2001, Howard and Cuffey 2006, Christian et al 2008, Vaughn et al 2008.…”
Section: The Interactions Between the Freshwater Pearl Mussel And Hosmentioning
confidence: 99%
“…In response to glochidia encystment, fish hosts have been shown to hyperventilate (Crane et al 2011), undergo haematological alterations (Meyers et al 1980) and exhibit immunological reactions (Alvarez-Pellitero 2008). The effects of these alterations include impaired gas exchange (Kaiser 2005), increased risk-taking (Godin and Sproul 1988), reduced foraging (Österling et al 2014) and competitive ability (Filipsson et al 2016), reduced swimming performance and, in cases of high infestation rates ( ~350 glochidia per gram fish weight or more), even mortality (Taeubert and Geist 2013). For example, glochidia encystment on largemouth bass ( Micropterus salmoides (Lacepède, 1802)) resulted in higher ventilation rates, reduced oxygen consumption and decreased tolerance of low-oxygen conditions for the host fish, suggesting that gill parasites can pose a respiratory burden for their hosts (Kaiser 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies reveal that FPM glochidia encystment can increase the recovery time required following a stressful event (Thomas et al 2014), induce an immune response (Thomas et al 2014), decrease foraging success (Österling et al 2014), negatively impact competitive ability (Filipsson et al 2016) and reduce the capacity for swimming (Taeubert and Geist 2013). Previous studies suggest that parasite infestation can have significant implications for the host.…”
Section: Introductionmentioning
confidence: 99%
“…There is also no agreement on how pathogenic the glochidia are while residing on juvenile salmonids (Cunjak and McGladdery, 1991). Because high loads of pearl mussel glochidia typically result in reduced swimming performance and increased mortality of brown trout hosts, and because there is a transfer of nutrients from the fish to the mussel involved, the relationship is considered parasitic (Taeubert and Geist, 2013;Taeubert et al, 2015). Most studies only measure the total glochidial loads on a fish host without considering the distribution of the glochidia.…”
Section: Introductionmentioning
confidence: 99%